SURVEY OF IMPLEMENTATION OF CURRICULUM-2013 IN CHEMISTRY TEACHING-LEARNING IN SLEMAN REGENCY SENIOR HIGH SCHOOLS - Nira Listyawati; KH.Sugiyarto KH.Sugiyarto (Universitas Negeri Yogyakarta, 2016)
The aims of the research were: (1) To know the degree of implementation of Curriculum 2013 in chemistry teaching-learning in Sleman Regency senior high schools in the aspect of (a) socialization of Curriculum 2013, (b) preparation of lesson plan, (c) teaching-learning process, and (d) evaluation. (2) To know the correlation between the socialization of Curriculum 2013 and (a) the preparation of the lesson plan, (b) teaching-learning process, and (c) the evaluation. (3) To identify the teacher’s problems in the implementation of Curriculum 2013 in chemistry teaching-learning process.This research was a quantitative descriptive research. The population was the High School chemistry teachers in Sleman Regency and the sample was 31 teachers chosen by using random sampling technique. The data were obtained by questionnaire. The data analysis was a quantitative descriptive technique using percentage analysis and product moment correlation analysis between socialization of Curriculum-2013 and preparation of lesson plan, teaching-learning process, and evaluation.The results of this research showed that the degree of implementation of Curriculum-2013 in chemistry teaching-learning of senior high schools in Sleman Regency in term of socialization of Curriculum-2013 was categorized as medium (64.19%), preparation of lesson plan was high (66.16%), teaching-learning process was high (73.72%), and evaluation was medium (63.58%). By using correlation product moment formula, there was significant correlation between socialization of Curriculum-2013 and preparation of lesson plan, learning process, as well as evaluation. Some constrains faced by chemistry teachers dealing with implementation of Curriculum-2013. These constraints were: form of lesson plan was unclear, socialization period was too short, many attachments should be included in the lesson plan, allocation time was too short, too many aspects exist in the assessment, and the number of students was plenty.